Factors Associated with Family Delays in Bringing Stroke Patients to Aloei Saboe Hospital, Gorontalo City - Muhammad Isman Jusuf; Zulkifli B Pomalango; Ibrahim Suleman (Jambura Nursing Journal, 2023)
Objective : Early arrival at the hospital for stroke patients provides the opportunity for fast and appropriate treatment, which is related to the success of treatment and improving patient clinical outcomes, while the clinical outcomes of stroke patients will get worse, if they do not get medical treatment quickly and precisely. Delay in handling the incidence of stroke, namely 83.9%, this was caused by delays in treatment at the prehospital stage. Purpose: To find out the factors associated with family delays in bringing stroke patients at Prof. Hospital. Dr. H. Aloei Saboe City of Gorontalo. Methods : Correlational analysis with cross sectional approach. The population in this study were the families of patients who cared for stroke patients at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City totaling 35 respondents, the sampling technique used purposive sampling technique. Results : There is a family empowerment system in optimizing prehospital management of stroke patients, which starts with identifying the factors that delay families bringing patients to health facilities, so that early treatment of patients can be carried out and can prevent disability and death. Conclusion : The three variables consisting of family knowledge, family attitudes and family support, are significantly positively related to delays in the patient's family bringing stroke patients to the Prof. Hospital Hospital. Dr. H. Aloei Saboe City of Gorontalo.